Standalone Single Stage PV-Fed Reduced Switch Inverter Based PMSM for Water Pumping Application - Prabhakaran, K. K.; Karthikeyan, A.; Varsha, S.; Perumal, B. Venkatesa; Mishra, Sukumar (IEEE transactions on industry applications, 2020)
This article proposes a standalone single stage photovoltaic (PV) fed reduced switch inverter (RSI) based permanent magnet synchronous motor (PMSM) drive for water pumping application. The proposed system aims at reducing the switching losses and overall cost by using reduced switch inverter. The proposed system comprises a PMSM drive, fed by PV source through an inverter employing reduced number of switches. The inverter uses only four switches whereas the conventional voltage source inverter utilizes six switches. Field oriented control scheme is employed to control the PMSM drive. Perturb and observe maximum power point tracking technique is used to generate a speed reference to PMSM drive. The proposed system is simulated using MATLAB/Simulink platform, and it is also experimentally verified with field programmable gate array (FPGA) controller based 400 W laboratory prototype PMSM drive. The simulation and experimental results demonstrate the efficacy of the proposed system.